1983
DOI: 10.1128/aem.46.4.930-940.1983
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nutrient deprivation on Vibrio cholerae

Abstract: Environmental and clinical strains of Vibrio cholerae were exposed to nutrient-free artificial seawater and filtered natural seawater microcosms for selected time intervals and examined for changes in cell morphology and number. Cells observed by transmission electron and epifluorescence microscopy were found to undergo gross alterations in cell morphology with time of exposure. The vibroid cells decreased in volume by 85% and developed into small coccoid forms surrounded by remnant cell walls. The initial num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(89 citation statements)
references
References 26 publications
7
82
0
Order By: Relevance
“…The two copiotrophic marine bacteria included in this study survive for long periods during nutrient and energy deprivation. The cells display a rapid size reduction during the first hours of starvation, which appears to be a common phenomenon in non-growing cells subsequent to an energy and nutrient downshift [5,7,8,10,18,25]. The lack of exogenous substrates results in a rapid decrease in endogenous respiration [12,13] and the nongrowing cells become totally dependent on cell material degradation to maintain cell integrity and viability [7,14,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two copiotrophic marine bacteria included in this study survive for long periods during nutrient and energy deprivation. The cells display a rapid size reduction during the first hours of starvation, which appears to be a common phenomenon in non-growing cells subsequent to an energy and nutrient downshift [5,7,8,10,18,25]. The lack of exogenous substrates results in a rapid decrease in endogenous respiration [12,13] and the nongrowing cells become totally dependent on cell material degradation to maintain cell integrity and viability [7,14,16].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to oligotrophs, copiotrophs are incapable of increasing their biomass during nutrient exhaustion but have the ability to survive without energy-yielding subtrates [1,4]. The lack of available substrates results in the formation of smaller cells [5][6][7][8][9][10][11], and a decrease in endogenous respiration [12,13]. To maintain a low endogenous metabolism, resting cells are dependent on protein, RNA, amino acid and/or storage polymer degradation [7,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Baker et al [15] reported that the exposure of V. cholerae to nutrient deprivation caused the cells (i) to become coccoid and lose over 90% of their original volume in 30 days, (ii) to increase in cell number, (iii) to lose small granules and inclusion bodies, (iv) to lose the distinct three-layered integrity of the outer membrane, peptidoglycan and the inner membrane to retain only remnants of those structures, (v) to compress the nuclear region into the center of the cell surrounded by a denser cytoplasm and (vi) to form extended or convoluted structures from the cell wall which are pulled away from the cell membrane. It has been suggested that these responses re£ect the existence of strategies to enhance survival under condition of exogenous nutrient deprivation [16^18].…”
Section: Gross Morphological Changes Of V Cholerae Upon Nutrient Stamentioning
confidence: 99%
“…Thè rounding up' phenomenon, with concomitant reduction in cell volume, and other necessary physiological changes are seen for Vibrio spp. under low-nutrient conditions [15,25,26].…”
Section: Gross Morphological Changes Of V Cholerae Upon Nutrient Stamentioning
confidence: 99%
“…Indeed, morphological and compositional alterations occur when bacterial cells are introduced into adverse environments (typically nutrient-depleted environments), for example, when enteropathogenic bacteria are released into waters through faecal contamination. These changes affect cell size, membrane and outer layer structure and secreted products (Baker et al 1983;Reeve et al 1984;Rollins and Colwell 1986;Decho 1990;Beumer et al 1992) and may reduce nucleic acid extraction efficiency.…”
Section: State Of Target Micro-organismsmentioning
confidence: 99%